HuR (Elavl1) and HuB (Elavl2) Stabilize Matrix Metalloproteinase-9 mRNA During Seizure-Induced Mmp-9 Expression in Neurons - Zybura-Broda, Katarzyna; Wolder-Gontarek, Malgorzata; Ambrozek-Latecka, Magdalena; Choros, Artur; Bogusz, Agnieszka; Wilemska-Dziaduszycka, Joanna; Rylski, Marcin (Frontiers in Neuroscience, 2018)
Matrix metalloproteinase-9 (Mmp-9) is involved in different general and cell-type–specific processes, both in neuronal and non-neuronal cells. Moreover, it is implicated in an induction or progression of various human disorders, including diseases of the central nervous system. Mechanisms regulating activity-driven Mmp-9 expression in neurons are still not fully understood. Here, we show that stabilization of Mmp-9 mRNA is one of the factors responsible for the neuronal activity-evoked upregulation of Mmp-9 mRNA expression in hippocampal neurons. Furthermore, we demonstrate that the molecular mechanism related to this stabilization is dependent on the neuronal seizure-triggered transiently increased binding of the mRNA stability-inducing protein, HuR, to ARE1 and ARE4 motifs of the 3’UTR for Mmp-9 mRNA as well as the stably augmented association of another mRNA-stabilizing protein, HuB, to the ARE1 element of the 3’UTR. Intriguingly, we demonstrate further that both HuR and HuB are crucial for an incidence of Mmp-9 mRNA stabilization after neuronal activation. This study identifies Mmp-9 mRNA as the first HuB target regulated by mRNA stabilization in neurons. Moreover, these results are the first to describe an existence of HuR-dependent mRNA stabilization in neurons of the brain.